Zirconocene-Catalyzed Dimerization of α-Olefins: DFT Modeling of the Zr-Al Binuclear Reaction Mechanism - Ilya Nifant’ev; Alexander Vinogradov; Alexey Vinogradov; Stanislav Karchevsky; Pavel Ivchenko (Molecules, 2019)
Zirconocene-mediated selective dimerization of α-olefins usually occurs when precatalyst (η5-C5H5)2ZrCl2 is activated by minimal excess of methylalumoxane (MAO). In this paper, we present the results of density functional theory (DFT) simulation of the initiation, propagation, and termination stages of dimerization and oligomerization of propylene within the framework of Zr-Al binuclear mechanism at M-06x/DGDZVP level of theory. The results of the analysis of the reaction profiles allow to explain experimental facts such as oligomerization of α-olefins at high MAO/(η5-C5H5)2ZrCl2 ratios and increase of the selectivity of dimerization in the presence of R2AlCl. The results of DFT simulations confirm the crucial role of the presence of chloride in the selectivity of dimerization. The molecular hydrogen was found in silico and proven experimentally as an effective agent that increases the rate and selectivity of dimerization.